Feminist sociology - Delamont, Sara, 1947- (Sage, 2003)
This book explores the achievements of British feminist sociology in theory, methods and empirical research. It outlines the barriers to the development of feminism and explores contemporary challenges. It provides an unrivalled guide to the origins of feminism in the discipline of sociology, analyses the uneasy relationships between feminists and the founding fathers and elucidates the opportunities and challenges presented by post-modernism.
Keywords: Feminist theory.; Sociology.; Sociology; Théorie féministe.; Sociologie.; sociology.; 71.38 social movements.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminist theory; Feminismus; Soziologie; Feminisme.; Feminismus.; Soziologie.; Feministische Soziologie.